Feminist Collections, v.25, no.1 (fall 2003) - (:unkn) unknown (My University, 2004)
Subtitle: A Quarterly of Women's Studies Reviews. 53p.
Contents: FROM THE EDITORS. BOOK REVIEWS: Bridges, Chasms, and Common Ground: Multicultural and Transnational Feminism, by Lynn Walter. Refusing False Choices: Feminist Responses to September 11, by Lynn Walter. The Spiritual Journeys of American Buddhist Women, by Alice Keefe. FEMINIST VISIONS: Women and Maquiladoras on the U.S.?Mexico Border, by Dionne Espinoza. FEMINIST ARCHIVES. WORLD WIDE WEB REVIEW: Feminism and Pregnancy on the Internet, by Karen Eckberg. E-SOURCES ON WOMEN & GENDER: By JoAnne Lehman. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard & Melissa Gotlieb. PERIODICAL NOTES: By JoAnne Lehman. ZINE AND HEARD (FOR THE THIRD TIME): By M.L. Fraser. SPOTLIGHT: A Feminist Library Zine, by Phyllis Holman Weisbard. ITEMS OF NOTE: By Melissa Gotlieb. BOOKS RECENTLY RECEIVED.
Keywords: Feminist Responses to September 11; Multicultural Feminism; Maquiladoras; Zines; American Buddhist Women; Gender; Transnational Feminism; E-Sources; Pregnancy; Library Resources; Reviews; Feminism; Women's Studies